WELL DRILLING AND DRILLING METHODS - SHUKUROV ABROR SHARIPOVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
This article describes the types of well drilling and general drilling. Ushbu maqola haqida quduqni anglash mumkin.